Hubungan Kekuatan Otot Lengan Dengan Kemampuan Pukulan Dropshot Dalam Permainan Bulu Tangkis Padamahasiswa Program Studi Pendidikan Olahraga STKIP Kie Raha Kota Ternate - Rifaid Saiman; Sukirman Masuku (Peneliti.net, 2023)
This study aims to determine the relationship between arm muscle strength and dropshot hitting ability in badminton games, as well as how much the two variables are related to each other. This research was carried out in the city of Ternate with a sample of 25 students. The population in this study were students of STKIP Kie Raha Ternate City. The method used is a survey with correlational analysis techniques. To obtain data on arm muscle strength by using the push up test while obtaining data on the ability to hit a drop shot using a test of hitting the ball in a predetermined direction. Data analysis uses the Pearson product moment formula at a significant level of α = 0.05/5%. The findings in this study show that: there is a significant relationship between arm muscle strength and dropshot hitting ability in badminton games for STKIP Kie Raha Students from Ternate City Class of 2018. The calculation results of data analysis of the two variables show that, r-count = 0.404> r-table 0.059 at a significant rate α = 0.05/5%. So it can be concluded that arm muscle strength can make a significant contribution to dropshot hitting ability